SISTEMA PARA EL CONTROL DE INVENTARIOS EN LA EMPRESA “INVERSIONES NOVILLO DE ORO S.A.S” - Jefferson Andrey Trujillo Leon (Revista Ingeniería, Matemáticas y Ciencias de la Información)
The purpose of this research work is to develop a proposal for the management of inventories in the Company«INVERSIONES NOVILLO DE ORO SAS» located in the city of Bogotá DC, since its processes and procedures do nothave a characterization under the criteria of international financial reporting standards, which translates into accountingrisks generated by the absence of an internal control system that detects and reduces them to a financially acceptablelevel, in such a way that it is urgent to use a tool that not only allows efficient inventory management, but satisfies theentity’s own needs.Taking into account that not any method for inventory control meets these requirements, given the existence of othercommonly used models such as the weighted average and ABC costing, however, these methods are used in industrialsectors, meanwhile, the case In particular, as the one in question focuses on the tertiary or services sector, specifically thegastronomic sector, it is important to remember that companies in this sector are distinguished by a daily rotation of theirinventories, especially those that require greater control such as perishables or at least a specific control, since theycould easily be carried as an expense, which is why it is the object of this research that aims to suggest the FIFO modelin order to avoid unnecessary costs and reduce waste, in relation to the administration of the resources, which we wellknow are scarce.